2018
DOI: 10.3390/nu10121866
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation of the Exercise-Snacking Licensing Scale: Rewarding Exercise with Unhealthy Snack Foods and Drinks

Abstract: There is evidence that individuals’ compensatory health beliefs may be an important psychological driver of health behavior. Only recently, however, have researchers begun to develop and seek to validate instruments that are suited to measuring specific pairings of the diverse compensatory health beliefs that exist. The aim of this study was to provide support for key aspects of validity associated with the Exercise-Snacking Licensing Scale (ESLS), an instrument that was designed to assess individuals’ endorse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Although we did not observe a significant difference in self-reported compensatory eating following the exercise training, we did note a trend for lower exercise snacking licensing post-training across the two groups. The consistency between groups was surprising given that previous work has shown that individuals driven by more autonomous (relative to controlled) motivation may experience lower compensatory licensing beliefs [ 16 ]. How these results related to the reduced snack intake following SIT is unclear at this stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not observe a significant difference in self-reported compensatory eating following the exercise training, we did note a trend for lower exercise snacking licensing post-training across the two groups. The consistency between groups was surprising given that previous work has shown that individuals driven by more autonomous (relative to controlled) motivation may experience lower compensatory licensing beliefs [ 16 ]. How these results related to the reduced snack intake following SIT is unclear at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two weeks prior to commencing training, each participant attended the laboratory for assessment of motivational orientation toward exercise (Behavioural Regulation in Exercise Questionnaire-3) [ 25 ], compensatory eating (Compensatory Eating Motives Questionnaire) [ 26 ], and post-exercise unhealthy snack licensing (Exercise Snacking Licensing Scale) [ 16 ]. Peak oxygen consumption was measured using a continuous graded exercise test on an air-braked front-access cycle, as described previously [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reveal that, for SRHI-low, the relationship between epistemic value and consumption of unhealthy food is not significant (p > 0.1), whereas, in SRHI-high, it is significant (p < 0.05) and the coefficient is 0.460. Specifically, although physical activity and its impact on appetite control and food intake are still unknown (Miguet et al, 2018), compensatory behaviour may be observed, and this may be an important psychological factor in healthy behaviour (West et al, 2018). This compensatory eating is defined as an increase in food intake after exercise or physical activity (Stein et al, 2016).…”
Section: Food Consumption Valuesmentioning
confidence: 99%
“…In support of this reasoning, Rabia et al 21 suggested that compensatory health behaviours are more likely to be present when individuals experience controlled motivation. Additionally, West et al 22 found that individuals scored lower on licensing beliefs around unhealthy snacking following exercise when they reported possessing more autonomous motivation for exercise, and that individuals driven by more controlled (relative to autonomous) motivation reported greater compensatory beliefs about food following 40 min of moderate-intensity cycling. 23 The second pathway articulated by Dimmock et al-that of impulsive processes-can be understood through theory and research on self-control.…”
Section: The Effect Of Psychological Experiences During Exercise On Energy Intake: a Role For Exercise Motivationmentioning
confidence: 99%